The Europeanization of national polities? citizenship and support in a post-enlargement union - Sanders, David, 1950- (Oxford : Oxford University Press, 2012)
This volume studies the levels and evolution of EU citizens' attitudes toward the EU by answering 3 key questions: How widespread is the sense of European citizenship? What are its core drivers? And what consequences does citizenship have, if any, for EU support and for active political participation in EU politics?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Citizenship -- Europe; European Union -- Public opinion; Europe -- Politics and government -- 1989-